2021
DOI: 10.1002/adfm.202103569
|View full text |Cite
|
Sign up to set email alerts
|

Activating Both Basal Plane and Edge Sites of Layered Cobalt Oxides for Boosted Water Oxidation

Abstract: Layered A x CoO 2 materials built by stacking layers of CoO 2 slabs and inserting alkali ions in between them have shown a promising activity of oxygen evolution reaction (OER) due to their active edge sites. However, the large basal plane areas of the CoO 2 slabs show too strong adsorption energy to the reaction intermediates, which is unfavorable for the release of O 2 . Here, a simple cation-exchange strategy based on Fe 3+ and alkali ions is proposed to simultaneously activate both the basal plane and edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
1
30
0
1
Order By: Relevance
“…It is demonstrated that in the anodic process the catalyst's surface experiences the electron rearrangement, which can accelerate the OER kinetics by modulating the adsorption energy for intermediates. [ 54 ] In the O 1s profiles in Figure S13b (Supporting Information), the binding energy slightly shifts in a negative direction after the stability test, suggesting the formation of the SO bond in sulfate form. [ 52 ] In the S 2p spectra (Figure S13c, Supporting Information), the peak positions present visible positive shifts relative to those in the initial Ni 2 Fe‐LDH/FeNi 2 S 4 , confirming the charge transfer from S to O.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that in the anodic process the catalyst's surface experiences the electron rearrangement, which can accelerate the OER kinetics by modulating the adsorption energy for intermediates. [ 54 ] In the O 1s profiles in Figure S13b (Supporting Information), the binding energy slightly shifts in a negative direction after the stability test, suggesting the formation of the SO bond in sulfate form. [ 52 ] In the S 2p spectra (Figure S13c, Supporting Information), the peak positions present visible positive shifts relative to those in the initial Ni 2 Fe‐LDH/FeNi 2 S 4 , confirming the charge transfer from S to O.…”
Section: Resultsmentioning
confidence: 99%
“…Water electrolysis is a potential method to generate carbon-free hydrogen from electricity and water if renewable electricity is used. For example, photovoltaic-driven electrolysis has benefits such as providing high efficiency, being cost-effective, and being part of an already commercially available system. , However, cost remains one of the main drawbacks in the success of hydrogen’s deployment, partly due to a lack of relevant mass manufacturing, in part due to a dependence on expensive raw materials. In this regard, alkaline water electrolysis (eqs and ) is a hydrogen production method, offering both technological maturity and the possibility to replace expensive precious-metal electrocatalysts (commercial benchmarks) with earth-abundant alternatives cutting costs without ruinous compromises in efficiency. This is true even for the oxygen evolution half-reaction (OER) (Figure ), which, being a multi-step proton-coupled electron-transfer reaction, is considered the bottleneck of overall water splitting. , …”
Section: Introductionmentioning
confidence: 99%
“…This method could be used for the online detection of chemical oxygen demand, photoelectrochemical immunoassay, and ROS-responsive payload release. However, due to the limitations of strong excitation sources and harsh experimental conditions in these systems, the inchoate loss of ROS leads to weak CL emission with the disadvantages of instability and low repeatability. Considering the stability of O 2 , the conversion and utilization of O 2 into ROS was a meaningful and challenging project. Therefore, to improve the photocatalytic generation of ROS in the catalysis in a mild condition, some aspects need to be considered, such as utilizing daylight to reduce the loss of ROS. …”
Section: Introductionmentioning
confidence: 99%